Psychedelics as Tools for Belief Transmission. Set, Setting, Suggestibility, and Persuasion in the Ritual Use of Hallucinogens - Dupuis, David (Frontiers in Psychology, 2021)
The use of psychedelics in the collective rituals of many indigenous groups suggests that these substances are powerful catalysts of social affiliation, enculturation and belief transmission. This feature has recently been highlighted as part of the renewed interest in psychedelics in euro-american societies, and seen as a previously underestimated vector of their therapeutic properties. The property of psychedelics to increase feelings of collective belonging and transmission of specific cultural values or beliefs raises however complex ethical questions in the context of the globalization of these substances. In the past decades, this property has been perceived as problematic by anticult movements and public authorities of some European countries, claiming that these substances could be used for "mental manipulation". Despite the fact that this notion has been widely criticized by the scientific community, alternative perspectives on how psychedelic experience supports enculturation and social affiliation have been yet little explored. Beyond the political issues that underlie it, the re-emergence of the concept of "psychedelic brainwashing" can then be read as the consequence of the fact that the dynamic through which psychedelic experience supports persuasion is still poorly understood. Beyond the unscientific and politically controversed notion of brainwashing, how to think the role of psychedelics in the dynamics of transmission of belief and its ethical stakes? Drawing on data collected in a shamanic center in the Peruvian Amazon, this article adresses this question through an ethnographic case-study. Proposing the state of hypersuggestibility induced by psychedelics as the main factor making the substances powerful tools for belief transmission, I show that it is also paradoxically in its capacity to produce doubt, ambivalence and reflexivity that psychedelics support enculturation. I argue that, far from the brainwashing model, this dynamic is giving a central place to the agency of the recipient, showing that it is ultimately on the recipient's efforts to verify the object of belief through an experiential verification process that the dynamic of psychedelic enculturation relies on. Finally, I explore the permanence and the conditions of sustainability of the social affiliation emerging from these practices and outline the ethical stakes of these observations.